Are similar control processes implemented during single and dual language production? Evidence from switching between speech registers and languages. Issue 3 (31st May 2020) - Declerck, Mathieu; Ivanova, Iva; Grainger, Jonathan; Duñabeitia, Jon Andoni
Abstract: To investigate whether similar control processes are used during single and dual language production, we compared register switching (formal and informal speech in the same language) vs. language switching (French and English). The results across two experiments showed a positive correlation of overall register- and language-switch costs and similar formal French switch costs across the two switching tasks. However, whereas increasing the cue-to-stimulus interval resulted in a reduction of language-switch costs, register-switch costs were unaffected by the interval manipulation. This difference in switch-cost pattern indicates that control processes are not entirely identical during single and dual language production.